Indian telecom regulatory framework in comparison with five countries: structure, role description and funding. Issue 1 (8th January 2018) - Hallur, Giri Gundu; Sane, Vivek S.
Abstract : Purpose: The purpose of this paper is to present a cross-country qualitative comparative analysis of telecom regulatory frameworks of five countries with that of India. Adopting an institutionalist approach, this paper contributes to understanding of how institutional frameworks in these five countries are structured as compared to that in India so as to ensure division of the authority and scope of the regulator vis-a-vis that of the ministry, and the bureaucracy; financial autonomy of the regulator; redressal of grievances of individual consumers; and modification in the framework to cater to convergence of telecom and broadcasting. Design/methodology/approach: The study is based on literature review of research papers, secondary research and documents published by the regulators of the five countries. The research methodology used is qualitative comparative analysis case-based research of five countries. The variables for comparison have been sourced from the World Bank Handbook for Evaluating Infrastructure Regulatory System . The researcher has adopted qualitative research method to bring forth the similarity, as well as the diversity in the regulatory setup of the five countries in comparison with India. Findings: Analysis reveals that there is an absence of clear role definition for policy formulating body, the DoT and the regulatory body, the TRAI. The involvement of a number of bodies leads to duplication of regulatory functions in the TRAI, DoT and the Telecom Commission. Secondly, with respect to standards, compliance and spectrum management, the TEC and WPC function as divisions of DoT; however, the TRAI is entrusted with ensuring interoperability among service providers as well as spectrum management. This leads to duplication of regulatory functions and absence of a single authority. Lastly, funding of the TRAI is done through the departmental allocation given to DoT alone with no additional funds coming in the form of regulatory fees. This is seen to be specific to TRAI as other sector regulators in India have been empowered to collect fees from industry participants. The Indian framework shows two commonalities in comparison with the five countries; firstly, India has adopted self-regulation through the setting up of the Telco-consumer group-led consumer redressal process. The second similarity being convergence of the regulatory functions performed by the TRAI for the telecom as well as the information and broadcasting ministries, although the two ministries continue to function independently. Originality/value: The paper furthers the understanding of the good practices in the design of telecom regulatory framework. It brings out the similarity and diversity in these frameworks. And, most importantly, it highlights limitations that the Indian telecom regulatory framework has in areas of role definition for the regulator, its autonomy and regulation of telecom-media convergence.